Treatment of nonocclusive mesenteric ischemia with type B aortic dissection using intra-arterial catheterization after trauma surgery: case report - Sho Fujiwara; Yuki Sekine; Ryuichi Nishimura; Kazuya Tadasa; Shukichi Miyazaki (Surgical Case Reports, 2018)
Abstract Background Nonocclusive mesenteric ischemia (NOMI) is a mesenteric arterial spasm and intestinal ischemia. This disease is a highly lethal disease because diagnosis and decision of appropriate treatments are often difficult. Operations cannot resolve the spasms and may worsen the situation. However, the safety and effectiveness of catheterization for NOMI with aortic dissection (AD) have not yet been elucidated. Here, we report a successful case of early diagnosis and treatment of NOMI with type B AD involving the superior mesenteric artery (SMA) using the intra-arterial infusion of a vasodilator via the SMA. Case presentation An 83-year-old man was admitted to our hospital because of abdominal pain after a motor accident. We performed intestinal resection and splenectomy for intestinal perforation and splenic hemorrhage and treated conservatively for acute AD, liver injury, renal hematoma, and pneumothorax. On postoperative day (POD) 2, the patient had localized abdominal pain. Follow-up computed tomography suggested a smaller superior mesenteric vein sign and segmental lack of enhancement in the intestinal wall and ascites without SMA occlusion. Thus, the patient was diagnosed with NOMI. Although the patient had type B AD including the SMA, we performed selective mesenteric arteriography and transcatheter papaverine infusion via the SMA and prostaglandin via the peripheral vein. Seven days post treatment, mesenteric blood flow improved and intestinal wall enhancement was restored. Conclusion The intra-arterial infusion of a vasodilator is highly efficient and safety treatment option for NOMI with type B AD. Prompt and accurate management can prevent massive small bowel resection, and this procedure is essential in resolving a spasm independent of whether a necrotic bowel has been resected.